Adult Migraine Hospital Admission Trends in Finland: A Nationwide Registry Study - Jussi O.T. Sipilä; Jori O. Ruuskanen; Päivi Rautava; Ville Kytö (MDPI, 2022)
Population-level data on migraine hospital admission trends are unavailable. Changes in stroke care may have influenced these, since migraine is one of the most common stroke mimics. In this study, all hospital admissions on neurological, internal medicine, and pediatric wards in Finland with migraine as the primary diagnosis for persons at least 16 years of age in 2004-2014 were studied, resulting in an analysis of 6195 individuals with 7764 migraine discharges. The number of discharges increased by 4.2% annually (p = 0.000084), with no change in age of the admitted patients. Comorbidity burden was low but increased during the study period (p < 0.0001). The frequency of common vascular risk factors as comorbidities increased by 11-19% annually. Admission duration shortened by 2% annually (p < 0.0001). An intravenous thrombolysis was given in four admissions. It seems that migraine hospital admissions have become more frequent and the patients more often have cardiovascular risk factors, suggesting increased awareness and more aggressive acute evaluation of suspected stroke as the cause.